All Days 2013
DOI: 10.2118/167529-ms
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Surfactant Polymer (Local) Enhanced Oil Recovery: An Experimental Approach

Abstract: Alkaline Surfactant Polymer (ASP) local oil recovery process has shown great potential in enhanced oil recovery (EOR). The recovery percentages are encouraging. The fact that these reagents are locally and cheaply sourced is also advantageous. The technique can be successfully applied in producing oil left in reservoirs after primary and secondary recovery process has been exhausted. The reagents used for this work include Irvingia Gabonensis, Lecithin and Palm Bunch Ash (PBA). Irvingia Gabonensis is granulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The result of an experimental work conducted by Khayati et al [23] using natural surfactant (saponin) showed that 5 g/L saponin reduced the interfacial tension and attained an additional oil recovery of 6-8% OOIP. Several researchers [25,26,28,30,40], reported the efficiency of some biomass based (agro-waste) chemicals as natural surfactant additives in displacing residual oil and increasing oil recovery between 19 and 23% OOIP.…”
Section: Introductionmentioning
confidence: 99%
“…The result of an experimental work conducted by Khayati et al [23] using natural surfactant (saponin) showed that 5 g/L saponin reduced the interfacial tension and attained an additional oil recovery of 6-8% OOIP. Several researchers [25,26,28,30,40], reported the efficiency of some biomass based (agro-waste) chemicals as natural surfactant additives in displacing residual oil and increasing oil recovery between 19 and 23% OOIP.…”
Section: Introductionmentioning
confidence: 99%
“…Alkalis used in chemical flooding interact with carboxylic acids in the crude oil generate in-situ surfactants, wettability alteration and reduce surfactant losses (Ojukwu et al, 2013). The alkali-oil chemistry is described by partitioning of the naphthenic acid between the oleic and aqueous phases and subsequent hydrolysis in the presence of alkali to produce a soluble anionic surfactant A …”
Section: Role Of Alkali In Chemical Eormentioning
confidence: 99%
“…Interestingly, recent studies reported the efficiency of certain natural products obtained from plant and animal sources (biobased surfactants) as preferred alternatives to conventional synthetic surfactants. Saponin-rich plant sources have been widely used due to their foaming ability. , Saponins are among the most abundant plant-based products and belong to the group of nonionic surfactants, which are mostly used as cosurfactants due to their high resistance to salinity and their capacity to improve surfactant–brine–oil phase behavior .…”
Section: Introductionmentioning
confidence: 99%